(untitled) (Annals of Bangladesh Agriculture, 2019)
Soil aggregate is one of the vital indicators of soil health that depends on organic carbon (OC), texture and basic cations. A total of 206 soil samples were collected from 12 agro-ecological zones (AEZs) of Bangladesh to study the effects of organic carbon (OC), basic cations (Ca, Mg, K and Na) and different sized soil particles on soil aggregate stability. Soil samples were analyzed for bulk density, pH, OC, texture, basic cations and water stable soil aggregates (WSA) following standard protocols. Data revealed that OC positively increased WSA, while monovalent basic cations Na+ and K+ showed negative effects. Water stable soil aggregates and C stock of 0.25 mm sized soil fraction were found higher than that of larger sized soil fractions of 0.5, 1.0 and 2.0 mm. The roles of divalent basic cations Ca2+ and Mg2+ on WSA were found to be indistinct and need to be studied further. Ann. Bangladesh Agric. (2019) 23(2) : 27-36